2012
DOI: 10.3126/kumj.v9i2.6282
|View full text |Cite
|
Sign up to set email alerts
|

The Glucose Challenge Test for Screening of Gestational Diabetes

Abstract: Background The frequency of gestational diabetes mellitus (GDM) is 0.6% -15% of pregnant woman. The modern trend towards the delay starting family is the main factor responsible for increase prevalence of GDM. This condition is associated with the adverse effect on mother and fetus, so it is important to find out the GDM by screening of all the pregnant women. Objective To observe the feasibility of using the 50g GCT for all pregnant women attending Dhulikhel Hospital, Obstetric OPD. To determine the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…In the present study, a 50-g oral GCT was conducted as part of a standard screening for GDM, as GCT is feasible, easy, user-friendly, cost-effective and convenient for screening purposes (22).…”
Section: B a B Amentioning
confidence: 99%
“…In the present study, a 50-g oral GCT was conducted as part of a standard screening for GDM, as GCT is feasible, easy, user-friendly, cost-effective and convenient for screening purposes (22).…”
Section: B a B Amentioning
confidence: 99%
“…Prevalence of GDM in a study done in Tribhuvan University Teaching Hospital (TUTH) Kathmandu was 0.6%, in Dhulikhel Hospital, it was 0.75% and in Kathmandu Medical College, it was 1.58%. [24][25][26] In all these studies screening test was done with 50 gm GCT and confirmation done with 75 gm OGTT. These studies were done long time back as compared to our study.…”
Section: Discussionmentioning
confidence: 99%
“…11 GDM is in increasing trend world wide, 7,12,14,15 and same can be seen in Nepal. [24][25][26][27][28][29] Maternal age is strongly associated with GDM. In many studies it was reported that prevalence of GDM is increased with maternal age.…”
Section: Discussionmentioning
confidence: 99%
“…This opinion has been shared by other investigators: Shrestha et al, concluded that the 50 g OGCT is a reliable test to detect GDM. This test is easy to administer and cost-effective for screening purpose [17]. A systemic review by van Leeuwen et al, in 2010 concluded that the 50-g OGCT is acceptable to screen for GDM [18].…”
Section: Discussionmentioning
confidence: 99%